The usefulness of global longitudinal peak strain and left atrial volume index in predicting atrial fibrillation in patients with ischemic stroke - Park, Soo-Hyun; Kim, Yerim; Lee, Minwoo; Lee, Sang-Hwa; Bae, Jong Seok; Lee, Ju-Hun; Kim, Tae Jung; Ko, Sang-Bae; Jeong, Sang-Wuk; Kim, Dong-Eog; Ryu, Wi-Sun (Frontiers in Neurology, 2024)
Introduction Detection of atrial fibrillation (AF) is crucial for preventing recurrence in patients with ischemic stroke. We aimed to examine whether the left atrial volume index (LAVI) and global longitudinal peak strain (GLPS) are associated with AF in patients with ischemic stroke. Methods We prospectively analyzed 678 consecutive patients with ischemic stroke. LAVI and GLPS were assessed using three-dimensional transthoracic echocardiography with speckle-tracking imaging. Multiple logistic regression was used to evaluate the association of AF with LAVI and GLPS. To evaluate the predictive value of LAVI and GLPS for the presence of AF, we used optimism-corrected c-statistics calculated by 100 bootstrap repetitions and the net reclassification improvement (NRI). Results The mean patient age was 68 ± 13 years (men, 60%). Patients with AF (18%) were a higher LAVI (41.7 ml/m2 vs. 74.9 ml/m2, P < 0.001) and a higher GLPS than those without AF (−14.0 vs. −17.3, P < 0.001). Among the 89 patients classified with embolic stroke of unknown source, the probable cardioembolic group had higher GLPS (n= 17, −14.6 vs. −18.6, respectively; P= 0.014) than the other groups (n= 72). Adding GLPS to age, hypertension, and the LAVI significantly improved the NRI, with an overall NRI improvement of 6.1% (P= 0.03). Discussion The LAVI andGLPS with speckle-tracking imaging echocardiography may help identify patients with AF.